1998
DOI: 10.1074/jbc.273.35.22458
|View full text |Cite
|
Sign up to set email alerts
|

The Putative Heparin-specific N-AcetylglucosaminylN-Deacetylase/N-Sulfotransferase Also Occurs in Non-heparin-producing Cells

Abstract: N-Deacetylation and N-sulfation of N-acetylglucosamine of heparin and heparan sulfate are hypothesized to be mediated by different tissue-specific N-acetylglucosaminyl N-deacetylases/N-sulfotransferases, which in turn lead to the higher L-iduronic acid and sulfate content of heparin versus heparan sulfate. Furthermore, the putative heparin-specific N-acetylglucosaminyl Ndeacetylase/N-sulfotransferase has been reported to require auxiliary proteins for its N-acetylglucosaminyl Ndeacetylase activity in vivo base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Indeed, a recent report by Grobe and Esko (Grobe and Esko, 2002) has highlighted a mechanism for post-transcriptional regulation of NDST expression in which the 3′-UTRs contain cryptic translation codons that might reduce the rate of translation. Three bands were observed on the NDST-2 blots, which is consistent with previous studies showing multiple NDST-2 transcripts (Kusche-Gullberg et al, 1998;Orellana et al, 1994;Toma et al, 1998). The observed high level expression of NDST-2 in the liver and mast cell lines is again consistent with results from a previous study (Orellana et al, 1994).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, a recent report by Grobe and Esko (Grobe and Esko, 2002) has highlighted a mechanism for post-transcriptional regulation of NDST expression in which the 3′-UTRs contain cryptic translation codons that might reduce the rate of translation. Three bands were observed on the NDST-2 blots, which is consistent with previous studies showing multiple NDST-2 transcripts (Kusche-Gullberg et al, 1998;Orellana et al, 1994;Toma et al, 1998). The observed high level expression of NDST-2 in the liver and mast cell lines is again consistent with results from a previous study (Orellana et al, 1994).…”
Section: Discussionsupporting
confidence: 91%
“…Four related NDSTs, NDST-1-NDST-4, have been identified (8 -12). Both NDST-1 and NDST-2 transcripts are widespread in different organs and cells (13,14), whereas the distribution of NDST-3 and NDST-4 appears to be more restricted (11,12).…”
Section: Heparan Sulfate (Hs)mentioning
confidence: 96%
“…63,64 The absolute requirement for NDST-2 in mast cell heparin biosynthesis was established in NDST-2 deficient mice, which have a normal life span and are fertile, but display a severe mast cell defect caused by a complete lack of sulfated heparin in the secretory granules. 65,66 Since, NDST-2-null mice show no signs of thrombosis, it is concluded that endogenous heparin is not involved in the regulation of coagulation, but instead plays a role in regulating the mast cell mediators, such as histamine and the mast cell-specific proteases (chymases and tryptases).…”
Section: B Heparan Sulfate (Hs) and Heparinmentioning
confidence: 99%